Impact of COVID-19 on the elderly: from lung aging to defense mechanisms: an integrative literature review: from lung aging to defense mechanisms - an integrative literature review (Brazilian Journal of Health Research, 2025)
Introduction: Elderly people were primarily the population most affected by the Pandemic of COVID-19, representing about 8.7% of deaths in the period from 2020 to 2022. Objective: To understand the impact of COVID-19 on the lung of the elderly, its clinical manifestations and the main defense mechanisms. Methods: Integrative literature review with an active search for information in the following databases: PubMed (National Library of Medicine), MEDLINE (Medical Literature Analysis and Retrieval System), Science Direct, Scielo (Scientific Electronic Library Online) and Portal de Periódico Capes/MEC, with bibliographic production between 2020 and 2022, based on the descriptors: "Elderly", "SARS-CoV-2", "Lung", based on the Health Sciences Descriptors (DeCS) using the booster element "AND". Review studies published in the period from 2020 to 2022 with older adults with a mean age ≥ 65 years were included, by articles with casuistries addressed outside Brazil, of both sexes, COVID-19 (SARS-CoV-2). The search was limited to English language publications and literature review articles and the methodology followed the PRISMA recommendations. Results: We identified ten (10) articles that met the inclusion criteria, (7) articles from the Science Direct database, two (2) from CAPES, and one (1) from PubMed. Conclusion: The progression of COVID-19 in the elderly population is due to the physiological and structural changes of the senescent lung, increasing the risk of Acute Respiratory Distress Syndrome (ARDS), exacerbating the clinical picture and making the elderly body more vulnerable to secondary infections with imminent risk of death.
Keywords: Elderly; Lung Injury; SARS-CoV-2